Optimizing the Role of Stakeholders in the Agricultural Intended HIV/AIDS Management in Jember District: Optimalisasi Peran Stakeholder Dalam Penanggulangan HIV/AIDS Berwawasan Agrikultura di Kabupaten Jember - Kurniawan, Dicky Endrian; Purwandari, Retno; Afandi, Alfid Tri; Khamid, M. Nur (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
One indicator of the effectiveness of HIV/AIDS prevention can be measured by the role of stakeholders involved in the HIV/AIDS prevention program. The obstacles are that there are still unequal perceptions of interest regarding the target group from each stakeholder in developing HIV/AIDS prevention programs and a lack of coordination between internal and external agencies, so there has been no effort to integrate programs between agencies. The purpose of this activity is to optimize the role of stakeholders in HIV AIDS prevention in Jember. This activity was carried out in stages (1) presenting material on "The Role of Stakeholders in HIV AIDS Response" and questions and answers related to the material presented, as well as (2) Focus Group Discussion (FGD) to discuss the implementation of the role of stakeholders in HIV AIDS response. The results of this activity show that stakeholders could understand the national strategy in dealing with HIV AIDS; stakeholders understood their role in HIV AIDS prevention, and stakeholder groups stated that they would help in the fight against HIV/AIDS. Definitive policy recommendations issued by local governments related to stakeholder involvement in HIV AIDS response.